ANALISIS DAMPAK PROGRAM LAKU PANDAI TERHADAP PERTUMBUHAN DANA PIHAK KETIGA, PERTUMBUHAN LIKUIDITAS DAN PERTUMBUHAN PROFITABILITAS - Arisma Huttamala Putri; Muhammad Yusuf (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
Amid of the development banking world; there are still people in village that have not received maximum banking services due to too far access and too much the existence of administrative costs that make people les interested in using banking services. There for OJK makes a laku pandai program for giving am access banking services and increasing financial inclusion in Indonesia. This research aims to obtain the empirical impact of laku pandai program that influence growth of dpk, growth of liquidty, and growth of profitability during periode 2013 to 2016. The sample of this research selected by purposive sampling and the number of sample is 96 banking development. Analyze technique be used in this research is PLS. The result of this research shows that laku pandai program has a positive significant effect on growth of dpk and growth of profitability, that has tstatistic value greater than ttable (ts > 1,96). While laku pandai program has no effect on growth of liquidity, that has tstatistic value smaller than ttable (0,907<1,96).